Phase boundaries, nucleation rates and speed of crystal growth of the water-to-ice transition under an electric field: a simulation study. (5th April 2018) - Zaragoza, Alberto; Espinosa, Jorge R; Ramos, Regina; Antonio Cobos, José; Luis Aragones, Juan; Vega, Carlos; Sanz, Eduardo; Ramírez, Jorge; Valeriani, Chantal
Abstract: We investigate with computer simulations the effect of applying an electric field on the water-to-ice transition. We use a combination of state-of-the-art simulation techniques to obtain phase boundaries and crystal growth rates (direct coexistence), nucleation rates (seeding) and interfacial free energies (seeding and mold integration). First, we consider ice Ih, the most stable polymorph in the absence of a field. Its normal melting temperature, speed of crystal growth and nucleation rate (for a given supercooling) diminish as the intensity of the field goes up. Then, we study polarised cubic ice, or ice Icf, the most stable solid phase under a strong electric field. Its normal melting point goes up with the field and, for a given supercooling, under the studied field (0.3 V nm −1 ) ice Icf nucleates and grows at a similar rate as Ih with no field. The net effect of the field would then be that ice nucleates at warmer temperatures, but in the form of ice Icf. The main conclusion of this work is that reasonable electric fields (not strong enough to break water molecules apart) are not relevant in the context of homogeneous ice nucleation at 1 bar.